THE DIFFERENT MENTAL HEALTH PATIENT QUALITY OF LIFE DURING SHACKLING, TREATMENT, AND POST TREATMENT - Arif Widodo; Supratman Supratman (Epidemiology and Society Health Review (ESHR), 2020)
Background: Mental health is a well-being mental state associated with happiness, joy, satisfaction, achievement, optimism, and hope. Good mental health allows a harmonious and productive life as an integral part of one's quality of life by taking into account all aspects of human life. This study aims to assess the different quality of life among mental health disorder patients during shackling, treatment, and post-treatment in Sukoharjo Regency.Methods: Quantitative descriptive was used in this study. Our population was all mental disorder patient in Sukoharjo District who has experienced with shackling and finished the treatment in the RSJD “dr Arif Zainudin," Surakarta during 2011-2015. We took total sampling and excluded patients who died, move to another place, and recover. Thirty out of thirty-four post-shackling patients in the Sukoharjo Regency participated in this study. A tested questionnaire was used to collect the data from the patient. The analysis was performed using univariate analysis – central tendency value analysis. Results: We found differences in patients' quality of life during shackling, treatment, and post-treatment. The survivor had the highest quality of life in the post-treatment phase compared to the shackled and treatment period.Conclusions: The quality of life of post-treatment patients is better compared during shackled and treatment.